2012
DOI: 10.1089/vbz.2011.0811
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Diversity of an Emergent Population ofBorrelia burgdorferiat a Coastal Maine Island Recently Colonized byIxodes scapularis

Abstract: The recent range expansion of Ixodes scapularis has been accompanied by the emergence of Borrelia burgdorferi. The development of genetic diversity in B. burgdorferi at these sites of emergence and its relationship to range expansion is poorly understood. We followed colonization of I. scapularis on a coastal Maine island over a 17-year period. B. burgdorferi's emergence was documented, as was expansion of ospC strain diversity. Ticks collected from rodents and vegetation were examined for the presence of B. b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
2
6
0
Order By: Relevance
“…Although the host community we sampled was primarily located at a single site, the pattern of ospC separation among phylogenetic groups may potentially be generalized, inasmuch as the frequencies of ospC types we detected in our host species were similar to those from other studies in the northeastern US and Canada (Brisson and Dykhuizen, 2004; Hanincova et al, 2006; Ogden et al, 2008, 2011; Barbour and Travinsky, 2010; MacQueen et al, 2012). Further investigation is warranted to determine whether the frequency patterns of HIS and non-HIS hold true for a larger number of host species, host individuals, and fed larval ticks in other areas where Lyme disease is endemic or expanding.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Although the host community we sampled was primarily located at a single site, the pattern of ospC separation among phylogenetic groups may potentially be generalized, inasmuch as the frequencies of ospC types we detected in our host species were similar to those from other studies in the northeastern US and Canada (Brisson and Dykhuizen, 2004; Hanincova et al, 2006; Ogden et al, 2008, 2011; Barbour and Travinsky, 2010; MacQueen et al, 2012). Further investigation is warranted to determine whether the frequency patterns of HIS and non-HIS hold true for a larger number of host species, host individuals, and fed larval ticks in other areas where Lyme disease is endemic or expanding.…”
Section: Discussionsupporting
confidence: 64%
“…Recent studies of associations between hosts and B. burgdorferi genotypes are limited by their focus on subsets of the hosts occurring at any single site, e.g., mammals or birds, but not both (Brisson and Dykhuizen, 2004; Alghaferi et al, 2005; Anderson and Norris, 2006; Hanincova et al, 2006; Ogden et al, 2008; but see MacQueen et al (2012) for an exception). Although there is some information on the transmission rates of B. burgdorferi from host to tick, based on needle and tick infections of mouse models in experimental inoculation studies, (Hofmeister et al, 1999; Hanincova et al, 2008; Baum et al, 2012), there is less information on transmission rates of strains from naturally infected wildlife host individuals to ticks.…”
Section: Introductionmentioning
confidence: 99%
“…We point out that the present study finds no evidence for the prediction found in the Lyme borreliosis literature that common oMG strains should decrease in frequency over time because they are preferentially targeted by the vertebrate immune system 22, 44, 45 . Previous studies on B. burgdorferi s. s. in I. scapularis ticks in the northeastern United States have documented rapid shifts in the prevalence distribution of the oMGs 17, 48, 49 . However, these studies were either done in tick populations where B. burgdorferi s. s. was emerging 48 or over shorter time periods (3 years) using less reliable methods (single-strand conformational polymorphism analysis) for detecting multiple oMG strains in ticks 17, 49 .…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies on B. burgdorferi s. s. in I. scapularis ticks in the northeastern United States have documented rapid shifts in the prevalence distribution of the oMGs 17, 48, 49 . However, these studies were either done in tick populations where B. burgdorferi s. s. was emerging 48 or over shorter time periods (3 years) using less reliable methods (single-strand conformational polymorphism analysis) for detecting multiple oMG strains in ticks 17, 49 . The present study of two sympatric Borrelia species is exceptional because of its long duration and because of its focus on a local population at a single small field site where Lyme borreliosis is endemic.…”
Section: Discussionmentioning
confidence: 95%
“…Co-feeding may be particularly important in the context of mixed infections where competition among strains will select for any additional transmission advantage. Previous studies have repeatedly shown that mixed infections of Borrelia strains are common in both the tick vector (Qiu et al 1997 , 2002 ; Wang et al 1999 ; Pérez et al 2011 ; MacQueen et al 2012 ) and the rodent reservoir (Brisson and Dykhuizen, 2004 ; Swanson and Norris, 2008 ; Pérez et al 2011 ; Andersson et al 2013 ). A recent experimental infection study found that there was genetic variation in co-feeding transmission among nine strains of B. afzelii (Tonetti and Gern, 2011 ).…”
Section: Adaptive Significance Of Co-feeding Transmissionmentioning
confidence: 99%